The mediterranean dietary pattern and breast cancer risk in Greek-Cypriot women: a case-control study - Demetriou, Christiana A (BioMed Central, 2012)
BACKGROUND: Diet has long been suspected to impact on breast cancer risk. In this study we evaluated whether the degree of adherence to a Mediterranean diet pattern modifies breast cancer risk amongst Greek-Cypriot women. METHODS: Subjects included 935 cases and 817 controls, all participating in the MASTOS case-control study in Cyprus. The study was approved by the Cyprus National Bioethics Committee. Information on dietary intakes was collected using an interviewer administered 32-item Food Frequency Questionnaire. Information on demographic, anthropometric, lifestyle, and other confounding factors was also collected. Adherence to the Mediterranean Diet pattern was assessed using two a-priory defined diet scores. In addition, dietary patterns specific to our population were derived using Principal Component Analysis (PCA). Logistic regression models were used to assess the association between the dietary patters and breast cancer risk. RESULTS: There was no association with breast cancer risk for either score, however, higher consumptions of vegetables, fish and olive oil, were independently associated with decreased risk. In addition, the PCA derived component which included vegetables, fruit, fish and legumes was shown to significantly reduce risk of breast cancer (ORs across quartiles of increasing levels of consumption: 0.89 95%CI: 0.65-1.22, 0.64 95%CI: 0.47-0.88, 0.67 95%CI: 0.49-0.92, P trend < 0.0001), even after adjustment for relevant confounders. CONCLUSIONS: Our results suggest that adherence to a diet pattern rich in vegetables, fish, legumes and olive oil may favorably influence the risk of breast cancer. This study is the first investigation of dietary effects on breast cancer risk in Cyprus, a country whose population has traditionally adhered to the Mediterranean diet.